Effect of Ketamine in Pulmonary Hypertensive Children - Pokharel, Jeju N; Upreti, M R; Shakya, D R; Regmi, Shyam Raj; Shakya, Urmila; Maskey, Arun (Nepalese Heart Journal, 2017)
Pulmonary hypertension is not an uncommon condition in clinical setting. Pulmonary artery (PA) pressure may increase during anesthesia because of the hypoxia, hypoventilation and acidosis. Keeping these factors constant there are also other possibilities which can increase the PA pressure, for example drugs. Among them ketamine is known to increase PA pressure in adults especially when they have baseline increased PA pressure. In few literatures it is claimed that in children ketamine may be safe even in those with pulmonary hypertension. We are using ketamine as a component of intravenous anesthesia in catheterization lab during right heart catheterization, pressure measurement and saturation evaluation. We thought it was necessary to evaluate the effect to ketamine on pulmonary artery pressure in pediatric patients in our setting. Altogether fifteen children diagnosed with pulmonary hypertension wer anesthetized with ketamine based anesthesia and the pulmonary artery pressure was evaluated in cardiac catheterization laboratory before and after 5, 10 and 15 min of injection of the ketamine (2mg/kg body weight) intravenously. We found in our study only about 6.2% increment in pulmonary artery pressure after 5 minutes of the injection of the ketamine and the pressure came to the pre-injection level at 10 to 15 minutes of the injection In conclusion of this preliminary study with limited number of the cases, ketamine can be used safely without much problems in pulmonary hypertensive children secondary to the increased blood flow to the lungs.